Analysis of high-perimeter planar electrodes for efficient neural stimulation - Wei, Xuefeng F.; Grill, Warren M. (Frontiers in Neuroengineering, 2009)
Planar electrodes are used in epidural spinal cord stimulation and epidural cortical stimulation. Electrode geometry is one approach to increase the efficiency of neural stimulation and reduce the power required to produce the level of activation required for clinical efficacy. Our hypothesis was that electrode geometries that increased the variation of current density on the electrode surface would increase stimulation efficiency. High-perimeter planar disk electrodes were designed with sinuous (serpentine) variation in the perimeter. Prototypes were fabricated that had equal surface areas but perimeters equal to 2, 3 or 4 times the perimeter of a circular disk electrode. The interface impedance of high-perimeter prototype electrodes measured in vitro did not differ significantly from that of the circular electrode over a wide range of frequencies. Finite element models indicated that the variation of current density was significantly higher on the surface of the high-perimeter electrodes. We quantified activation of 100 model axons randomly positioned around the electrodes. Input-output curves of the percentage of axons activated as a function of stimulation intensity indicated that the stimulation efficiency was dependent on the distance of the axons from the electrode. The high-perimeter planar electrodes were more efficient at activating axons a certain distance away from the electrode surface. These results demonstrate the feasibility of increasing stimulation efficiency through the design of novel electrode geometries.